Pengaruh Independensi, Kecerdasan Emosional, Pengalaman Kerja, dan Pelatihan pada Kinerja Pengawas Koperasi di Kota Denpasar - Maharani, Ni Luh Made Pinggaditya; Mimba, Ni Putu Sri Harta (Jurnal Samudra Ekonomi dan Bisnis, 2025)
Cooperatives play a vital role in the national economy, but their effectiveness depends on the performance of cooperative supervisors. This study aims to analyze the influence of independence, emotional intelligence, work experience, and training on the performance of cooperative supervisors in Denpasar City. This study used a quantitative approach with a sample of 97 cooperative supervisors selected using proportionate stratified random sampling. Data were collected using an online questionnaire and analyzed using multiple linear regression with SmartPLS software. The results indicate that the four variables, that isx: independence, emotional intelligence, work experience, and training, have a positive and significant influence on the performance of cooperative supervisors.